Together for Health: An Initiative to Access Health Services for the Hispanic/Mexican Population Living in the United States - Rangel Gómez, María Gudelia; López Jaramillo, Ana María; Svarch, Alejandro; Tonda, Josana; Lara, Juanita; Anderson, Elizabeth J.; Rosales, Cecilia (Frontiers in Public Health, 2019)
A disproportionately small percentage of the Hispanic/Mexican population in the United States has adequate access to health services, which decreases quality of life at both the individual and community levels. In addition, it increases risk for preventable diseases through insufficient screening and management. The Mexican Section of the U.S./Mexico Border Health Commission, in efforts to address barriers to accessing preventive health care services for vulnerable populations, launched the initiative Juntos por la Salud (JPLS) that offers health promotion and disease prevention services to Hispanics living in and around 11 U.S. metropolitan cities via mobile health units. This paper presents a descriptive analysis of the JPLS initiative and potential positive impact it has had in reducing barriers faced by the Hispanic population. JPLS screens and provides referrals to primary care services to establish a medical home and has the potential to reduce health care costs in a high-risk population through education and timely health screenings.